An Analysis of Students’ Ability in Writing Analytical Exposition Text - Zuliani Zuliani; Genta Sakti (Journal of English Language and Education, 2021)
This research aim at describing the second grade students’ writing ability in analytical exposition text SMA N 1 Canduang. The researcher uses descriptive quantitative research design. This study concerns on analytical exposition text. Which are written by XI class of SMA N 1 Canduang. The total population was 100 students’, distributed into four classes, 2 classes of IPA and 2 classes IPS. 2 IPA and 2 IPS were used as research sample, the four classes’ consisted of 25 students. The result of the data analysis showed that the students’ writing ability on an analytical exposition text at SMA N 1 Canduang was good. Base on the result there are one students’ who are in poor level, four students’ in moderate level, and then, five teen students’ in Good level. At last, one students’ in Very Good level. Overall, the ability of the eleventh grade of Senior High School 1 Canduang is in proficient level.